2008
DOI: 10.1002/cm.20286
|View full text |Cite
|
Sign up to set email alerts
|

The spindle function of CDCA4

Abstract: In an attempt to discover novel proteins functioning in both interphase nucleus and mitotic spindle as NuMA does, we carried out cDNA library screening with pooled autoimmune antibodies. Among positive clones we found a recently identified transcription regulatory protein (CDCA4) with the distinctive nuclear-mitotic apparatus distribution. CDCA4 localizes at metaphase spindle poles and the midzone in later stages. Additionally, an intensive CDCA4 accumulation parallel to spindle was observed in half of metapha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The present study aimed to examine the effect of RNA interference targeting CDCA4 on cell proliferation, cell cycle progression and apoptosis in the MCF-7/ADM human breast cancer cell line. A couple of studies ( 10 , 17 ) have revealed that CDCA4 regulates cell proliferation in a variety of cancer cells. However, the effect of the expression of CDCA4 on the growth of breast cancer cells remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to examine the effect of RNA interference targeting CDCA4 on cell proliferation, cell cycle progression and apoptosis in the MCF-7/ADM human breast cancer cell line. A couple of studies ( 10 , 17 ) have revealed that CDCA4 regulates cell proliferation in a variety of cancer cells. However, the effect of the expression of CDCA4 on the growth of breast cancer cells remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Cell division cycle-associated protein 3 (CDCA3), which is referred to as a “trigger” of mitotic entry ( 15 ), mediates destruction of the mitosis-inhibitory kinase wee1 as a part of S phase kinase-associated protein 1/Cullin 1/F-box (SCF) E3 ubiquitin ligase complex ( 16 ). Cell division cycle-associated protein 4 (CDCA4) is involved in spindle organization from prometaphase and depletion of CDCA4 can result in accelerated cell proliferation ( 17 ). Cell division cycle-associated protein 5 (CDCA5) is an essential component for the stable binding of chromatids during S and G2/M phases and the maintenance of DNA strands’ stability during G2 phases ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…From prometaphase onwards, CDCA4 is involved in spindle organization. CDCA4 may perform a distinct function as a midzone factor engaged in chromosomal segregation or cytokinesis when anaphase starts ( 24 ). Uncontrolled growth and invasion were considered as the most dangerous pathological alterations underneath the intricacy and idiopathy of every malignancy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%